Integrating GeoAI-based marine conservation with fiqh and usul al-fiqh: a review - Ridzuan, Nurfairunnajiha; Nawi, Mohd Firdaus; Abdullah, Najatul Su Ad; Abdul Razak, Rashidah; Mohamed, Juliana (Russian Law Journal, 2026)
Marine ecosystems are increasingly threatened by climate change, unsustainable fishing, coastal development, and pollution, necessitating more sophisticated and value-driven approaches to conservation. Geospatial Artificial Intelligence (GeoAI), which integrates GIS, remote sensing, and artificial intelligence, has emerged as a powerful tool for marine environmental governance through its capabilities in spatial analysis, environmental monitoring, predictive modelling, and decision support. At the same time, the Islamic disciplines of Fiqh and Usul al-Fiqh offer a comprehensive ethical and legal framework grounded in principles such as khilāfah (stewardship), mīzān (balance), maqāṣid al-sharīʿah (higher objectives of Islamic law), maṣlaḥah (public interest), and sadd al-dharī‘ah (blocking the means to harm). This paper conceptually explores the integration of GeoAI with Islamic jurisprudential principles to develop a holistic framework for marine conservation. It first outlines key GeoAI applications and then examines how Fiqh and Usul al-Fiqh can guide the ethical use of these technologies, particularly through maqasid-oriented governance and preventive approaches informed by sadd al-dharī‘ah. The study concludes that GeoAI can serve as an effective instrument to operationalise Islamic environmental ethics by providing empirical evidence for ethically grounded policy decisions. The proposed integration strengthens both scientific robustness and moral legitimacy in marine governance, especially in Muslim-majority contexts, and highlights future directions for institutional frameworks, capacity-building, and interdisciplinary collaboration.